Endodontic Management of Mandibular First Molar with Middle Distal Canal: A Case Report - Vijay Reddy Venumuddala; M. Sridhar; M. Rajasekaran; Saravanan Poorni; Gnanaprakasam Senthilkumaran (Case Reports in Dentistry)
The knowledge of variations in root canal morphology is critical for a successful endodontic treatment. This article presents the endodontic management of a unique case of mandibular molar with middle distal canal which is quite uncommon.